ANALISIS PRODUKTIFITAS PENGGUNAAN ALAT BERAT EXCAVATOR PADA PENAMBANGAN PASIR DI DESA KEDIRI KECAMATAN KEDIRI KABUPATEN LOMBOK BARAT - LEONARDUS BANGGUR; LALU HARDY WIJAYA; AMINULLAH AMINULLAH; KUSMIANTI KUSMIANTI (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2023)
The purpose of this research is to find out the productivity of the excavator and to know the operational and maintenance costs and to know the cost of renting an excavator. This type of research is a case study using a quantitative descriptive statistical approach. This study took the location/area in Kediri Village, Kediri District, West Lombok Regency. This research was conducted in July 2022. Data processing and analysis included costs of heavy equipment productivity, heavy equipment rental costs, heavy equipment maintenance and operational costs. The results showed that the productivity of the heavy equipment excavator Hyundai Robex 220-9SH in sand mining work in the village of Kediri for digging 1,336 ????3 / ????????????, digging 167 m3 of sand for 8 hours 1,336 m3, 9,352 m3 for 7 days. The productivity of the excavator to move sand to the dump truck is 95.52 ????3 / ???????????? as much as 191.04/day. Mobility and demobilization of IDR 3,000.00. The price for renting an excavator for 7 days is IDR 9,800,000. Fuel/diesel for 7 days as much as IDR 3,472,000. The operator's salary for 7 days is IDR 1,225,000. The total productivity cost of the excavator heavy equipment per week is Rp. 17,497,000. Based on the results of heavy equipment calculations in the original (existing) field conditions using 2 units of excavators, the total rental fee for each is IDR 34,994,000/week.